Airport '77 - Jameson, Jerry; Vaccaro, Brenda, 1939-; Jack Lemmon; Joseph Cotten; Lee Grant (USA Universal Pictures, 1977)
A luxury 747 carrying valuable art work is hijacked and lands in the ocean, submerged in shallow water. Will the crew and passengers make it off before the plane floods with water?
Art thieves hijack a 747, hit fog and crash into the ocean, trapping them and the passengers under 100 feet of water.
H.A.L. Craig
Languages : English, German, French, Spanish, Italian Subtitles : English, German, French, Spanish, Italian
Keywords: Action; Thriller; Drama